2006
DOI: 10.1016/j.jhep.2006.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide change of codon 38 in the X gene of hepatitis B virus genotype C is associated with an increased risk of hepatocellular carcinoma

Abstract: The codon-38 change in genotype C is an independent risk factor for the development of HCC and may serve as a useful molecular marker for predicting the clinical outcomes in patients infected with HBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 38 publications
2
51
5
Order By: Relevance
“…These 'hot-spot' mutations are located in the carboxy functional region, and thus might be associated with the transactivating function of the X protein [32]. Previous studies also reported that other amino acid substitutions, such as A36T, P38S, A44L, and H94Y were significantly associated with the risk of HCC [11,15,33,34]. However, the prevalence of these mutations, except A36T, was found to be relatively low in our study and there was no significant difference in their prevalence between the HCC and non-HCC group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These 'hot-spot' mutations are located in the carboxy functional region, and thus might be associated with the transactivating function of the X protein [32]. Previous studies also reported that other amino acid substitutions, such as A36T, P38S, A44L, and H94Y were significantly associated with the risk of HCC [11,15,33,34]. However, the prevalence of these mutations, except A36T, was found to be relatively low in our study and there was no significant difference in their prevalence between the HCC and non-HCC group.…”
Section: Discussionmentioning
confidence: 97%
“…The X protein is a multifunctional regulator that modulates host transcription, cell cycle progress, protein degradation, apoptosis, and signal transduction pathways [14]. It has been shown that mutations in the X gene may contribute to the development of HCC in HBV-infected patients [15,16]. In addition, mutations in the BCP region, which overlaps the coding sequence for the X gene, may result in amino acid changes in the X protein [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Taiwan reported that the amino acid substitution at codon 31 of HBx protein (S31A) was frequently found in HCC patients and was predicted to have an association with HCC development [33] . A Japanese group also reported that a mutation at codon 38 (P38S) of HBV genotype C was associated with HCC development [34] . Recently, it was reported that mutations in HBx protein (V5M/L, P38S, H94Y, I127T/N, K130M www.wjgnet.com and V131I) from Korean patients are linked with severity of liver disease [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some mutations in HBx protein, in particular for HBV genotype C, have been shown to be significantly associated with HCC. A Serine-toAlanine mutation at codon 31 (S31A) in HBx protein [33] , a Proline-to-Serine mutation at codon 38 (P38S) in HBx protein of HBV genotype C [34] , and some other particular mutations in HBx protein were found to be associated with increased risk of HCC [35] . Those studies, however, were independently carried out in different countries (China Taiwan, Japan, and Korea), and resulted in three different results.…”
Section: Introductionmentioning
confidence: 99%
“…HBx protein promotes virus gene expression and replication by trans-activating the virus promoters and enhancer/promoter complexes [39,40]. In addition, HBx accumulation enhances viral replication by altering various cellular activities including aberrant expression of molecules, involved in host cell signal transduction, transcription and proliferation, leading to viral persistence and hepatocarcinogenesis [41,42,43].…”
Section: Hepatitis B X Antigen (Hbxag)mentioning
confidence: 99%